Should I stay or should I go? : a guide to knowing if your relationship can--and should--be saved - Bancroft, Lundy (Berkley Trade, 2011)
Every relationship has problems, but you can't figure out if yours is beyond hope. How bad is too bad--and can your man really change? Now, in this warm, supportive, and straightforward guide, Lundy Bancroft and women's advocate JAC Patrissi offer a way for you to practically and realistically take stock of your relationship and move forward. If you're involved in a chronically frustrating or unfulfilling relationship, the advice and exercises in this book will help you.